2015
DOI: 10.7250/eb.2014.022
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Company Reputation and its Customer-Oriented Culture for Strengthening of Relationships with Customers on Industrial Market with Chemical Products

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…The findings of this study indicate that service quality has a positive effect on customer satisfaction. This is consistent with the view (Lostakova & Stejskalova, 2015) that company management recognizes the need to build a company reputation and customer-centric culture through service quality as the foundation for enhancing relationships with stakeholders, particularly customers. According to the majority of research on service quality, client satisfaction is the most influential factor in determining service quality.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The findings of this study indicate that service quality has a positive effect on customer satisfaction. This is consistent with the view (Lostakova & Stejskalova, 2015) that company management recognizes the need to build a company reputation and customer-centric culture through service quality as the foundation for enhancing relationships with stakeholders, particularly customers. According to the majority of research on service quality, client satisfaction is the most influential factor in determining service quality.…”
Section: Resultssupporting
confidence: 86%
“…Compared to the other three components of service quality, this study reveals that compliance has the highest impact on overall service quality. A company's solid reputation and customer-centric culture serve as the foundation for fostering closer relationships with customers and other stakeholders (Lostakova & Stejskalova, 2015). To exist as a socially cohesive species, humans require a shared system of ideas, practices, and values that direct their behavior toward a shared objective or the maintenance of generally accepted conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Companies that adopt a customercentric approach are more likely to provide quality service, enhance customer satisfaction, and achieve organizational objectives more efficiently and effectively (Cano et al, 2004). In a quantitative study of B2B marketing firms in the chemical industry, researchers found that a culture emphasizing customer orientation strengthens customer relationships and equips firms to navigate the challenging market landscape more adeptly (Lostakova & Stejskalova, 2014). Consequently, it can be theorized that the strategic orientations of board members demonstrate a statistically significant connection with customer focus.…”
Section: Literature Reviewmentioning
confidence: 99%